Study on the impact of vegetation change on ecosystem services in the Loess Plateau, China - Haihong Qiu; Jiaying Zhang; Hairong Han; Xiaoqin Cheng; Fengfeng Kang (Ecological Indicators, 2023)
Vegetation change has a non-negligible role in the impact of ecosystem services (ESs). Quantitative assessment of vegetation ecosystem services is the basis for sustainable regional development. Using the Chinese Loess Plateau (LP) as the study area, this study firstly analysed the spatial and temporal characteristics of vegetation change and used a Geodetector model to reveal the driving mechanism. Next, this study applied the InVEST model to quantitatively assess the four services of carbon storage, habitat quality, soil conservation and water yield, and explored the vegetation ecosystem service balance through vegetation type transfer. The results showed that (1) there was a trend towards an increase in the area of all vegetation types, with sparse vegetation being the most pronounced. Areas of damaged vegetation were concentrated in urban and peripheral areas, as well as wasteland and bare ground. (2) Annual precipitation, soil types and cumulative afforestation area ratio were the main drivers of vegetation change on the LP. (3) Restoration of woodland enhanced carbon storage, habitat quality and soil retention services for vegetation on the LP, while water yield decreased by 31.66%. The restoration of vegetation area did not enhance all ecosystem services. This study may provide a reference and basis for the sustainable management of regional ecosystems.